Effectiveness of Digital Identity (IKD) Services in Public Administration: A Case Study of Bandung City - Ginanjar Wira Saputra; Cecep Suarha; Rahma Triadi (Universitas Muhammadiyah Sidoarjo, 2026)
Although digital governance promises to streamline public administration, the transition to Digital Population Identity (IKD) often encounters adoption barriers at the local government level, creating a gap between digital policy intentions and actual community utilization. To address this gap, this study aims to analyze the effectiveness of the IKD service implemented by the Civil Registry Office (Disdukcapil) of Bandung City. Employing a qualitative case study approach, data were gathered through in-depth interviews with Disdukcapil officials and users, direct observations, and document analysis. The findings reveal that while IKD significantly enhances service efficiency by reducing processing time, its overall effectiveness is hindered by low digital literacy, infrastructure disparities, and societal resistance to change. As a primary contribution, this research highlights that successful digital transformation in public services extends beyond mere technological deployment; it necessitates a holistic alignment of institutional capacity, human resource competence, and community readiness. Therefore, it is recommended that local governments intensify inclusive public outreach, facilitate targeted digital literacy programs, and upgrade supporting infrastructure to ensure the sustainability of digital identity services.